Response time to estrus synchronization - R.R. Schalles; M. Spire; C. Clarke (Kansas Agricultural Experiment Station Research Reports, 1983)
Heavy milking cows took longer to respond to estrus synchronization than light milking cows. There was no difference in response time between cows treated with Estrumate and Lutalyse. Cow weight, height or condition had no effect on estrus response time.
Keywords: Cattlemen' s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Estrus; Milk production